2009
DOI: 10.1177/1053451208326054
|View full text |Cite
|
Sign up to set email alerts
|

Developing Behavioral Fluency for Students With Autism

Abstract: With the increase of students with autism in public schools, alternative schools, and in-home programming, attention to effective learning procedures has increased. A general model based on precision teaching for practicing behavior to fluency is presented as a guide for teachers and parents. This model applies to a wide variety of skills and can be tailored for individual students. The procedure for conducting efficient practice fall into four broad categories: (a) planning the practice routine, (b) developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The careful definition and monitoring of behaviour using PT allows for the ascertainment of individual differences in performance and the development of behavioural fluency. Components of an intervention incorporating PT typically include: (1) establishing a criterion rate for performance of the targeted skill (ie, a time in which an expert can comfortably complete the behaviour with total accuracy); (2) providing opportunities to practice the behaviour in the context of timed trials and delivering feedback regarding errors and speed of performance (referred to as frequency building); (3) charting of the data from trials using the standard celeration chart, and; (4) changing teaching tactics when the standard celeration chart indicates that performance is not improving 14. Interventions incorporating PT typically include many of the elements of mastery learning6 and deliberate practice16 including baseline testing, the targeting of a clearly defined behaviour, the provision of corrective feedback and the continuation of practice until a passing standard is achieved 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…The careful definition and monitoring of behaviour using PT allows for the ascertainment of individual differences in performance and the development of behavioural fluency. Components of an intervention incorporating PT typically include: (1) establishing a criterion rate for performance of the targeted skill (ie, a time in which an expert can comfortably complete the behaviour with total accuracy); (2) providing opportunities to practice the behaviour in the context of timed trials and delivering feedback regarding errors and speed of performance (referred to as frequency building); (3) charting of the data from trials using the standard celeration chart, and; (4) changing teaching tactics when the standard celeration chart indicates that performance is not improving 14. Interventions incorporating PT typically include many of the elements of mastery learning6 and deliberate practice16 including baseline testing, the targeting of a clearly defined behaviour, the provision of corrective feedback and the continuation of practice until a passing standard is achieved 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…These results are also in parallel with the reading and writing literature. Kubina and Wolfe (2005) similarly observed that the existence or lack of endurance has an impact on writing performance. Accordingly, it was observed that the students with endurance maintained their performance on a certain level while the students without the endurance lost the performance after a while.…”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, an athlete who has the endurance runs a given distance at a certain pace and does not get tired. He/she can maintain the speed at the beginning until the end of the race (Kubina & Wolfe, 2005). Similarly, a student who has the endurance in reading can deliver a performance at a fixed rate (Binder, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We really do not know the aims that produce such desirable outcomes as retention, endurance, application, and adduction (Johnson & Layng, 1996;Kubina & Wolfe, 2005). In this regard, consider the follow-up performances of the fluency-trained participants.…”
mentioning
confidence: 99%
“…We focused on response rates because a growing literature (e.g., Binder, 1996;Bucklin, Dickinson, & Brethower, 2001;Kubina & Wolfe, 2005) suggests that procedures that promote fluency can promote important learning outcomes, such as retention (i.e., appropriate, high-rate behavior persists long after training is completed), endurance (i.e., appropriate, high-rate behavior persists for durations greater than the durations of practice sessions), application (i.e., behavior can easily combine with other behaviors to form composites), and adduction (i.e., behaviors combine to form new behavior with little or no additional instruction). Presumably, procedures that produce many fluent editing skills could help editors easily eliminate previously encountered and novel stylistic problems, long after training (Binder, 2004; see the discussion of fluency by Johnson & Layng, 1996).…”
mentioning
confidence: 99%